Ketahanan Keluarga dalam Persfektif Hukum Islam di Masa Pandemi Covid-19 - Mesta Wahyu Nita (Al Qadhi Journal of Islamic Family Law, 2022)
Disasters and disasters are a necessity that must be faced by every human being. As a believer, regardless of the form of disaster, it will be interpreted as a form of God's love for his people and creatures. As an event that befell mankind, it is essentially a test and trial for mankind's faith as caliph on earth. The monotheism of Muslims will be determined by the events that befall humans, it's just a matter of how to react to the test. The disharmony factor in the family is one of the causes of the breakdown of family communication and will lead to divorce between husband and wife. Disharmony can be caused by a shift in marital values. Couples do not understand the essence and purpose of marriage, having a family which is one of the values ​​in family resilience. Family resilience is one of the factors of harmony in the household. This will have implications for harmony in the social community where it is located. Household values ​​based on religious values ​​need to be understood as a shared need in the family. Family harmony and happiness which is one of the goals can be realized.